Spatial distribution of Greenland halibut Reinhardtius hippoglossoides in relation to abundance and hypoxia in the estuary and Gulf of St. Lawrence - Youcef, Wahiba Ait; Lambert, Yvan; Audet, Céline (Fisheries Oceanography, 2013)
Annual bottom‐trawl surveys (1990–2010) were used to examine associations between environmental conditions, spatial distribution, and size‐specific abundance of Greenland halibut Reinhardtius hippoglossoides in the estuary and Gulf of St. Lawrence (EGSL), and to test the influence of hypoxic conditions on habitat selection. Size classes representing juvenile, immature and adult fish were used for the analyses. The highest concentrations of fish were found in the St. Lawrence estuary at both high and low levels of stock abundance. The areas occupied by 50, 75, and 95% of juvenile fish expanded with higher population abundance. However, contrary to our predictions, densities in marginal habitats did not increase at a higher rate than in optimal habitats. Fish longer than 32 cm were distributed over a broader area than juvenile fish. Their abundance explained a limited proportion of the variability in spatial distribution. The spatial dynamics of Greenland halibut in the EGSL is best described by a proportional density model where the rate of increase in local density is associated with population abundance. Habitats selected by Greenland halibut were characterized by low dissolved oxygen (DO) levels. The strong association between high fish densities and low DO concentrations indicates a high tolerance of Greenland halibut to hypoxia. It also indicates that negative effects, if present, could be compensated by other factors such as food availability and/or refuge from predation. The results of this study also clearly define the St. Lawrence estuary as the major nursery area for the EGSL population. -- Keywords : Density dependence, Estuary and Gulf of St. Lawrence spatial distribution habitat selection, Greenland halibut, Hypoxia.